Вы находитесь на странице: 1из 62

6

1.
1.1. :
1.2.
1.3.
1.4.
1.5.
-1First Prev Next Last Go Back Full Screen Close Quit

15 ( )
f C 1(Rn),
f (x) f > ,
f 0(x):
kf 0(x) f 0(y)k L kx yk
0 <
< 2/L. f 0(xk ) 0 k
f (xk+1) f (xk ),
x0.
-2-

First Prev Next Last Go Back Full Screen Close Quit

f ( l > 0),
x y Rn
f (x + y) f (x) + hf 0(x), yi + lkyk2/2.
(37)
10. f
( l > 0),
Rn.
-2First Prev Next Last Go Back Full Screen Close Quit

11. f ( l > 0) x
, x Rn
kf 0(x)k2 2l(f (x) f (x)).

-3First Prev Next Last Go Back Full Screen Close Quit

16 ( )
f Rn,
,
f 0(x) : kf 0(x)f 0(y)k L kx
yk 0 <
< 2/L.
xk x k kxk
xk Cq k , 0 q < 1.
-4First Prev Next Last Go Back Full Screen Close Quit

f

.
: f xk
: q(x) = f (xk ) + f 0(xk )(x
xk ) + 12 (x xk )>f 00(xk )(x xk ).
xk+1
q(x) ( ).
-5First Prev Next Last Go Back Full Screen Close Quit

, f 00(xk )
= q(x)
= =

q 0(xk+1) = 0, q(x)

f 0(xk ) = f 00(xk )(xk+1 xk ).

-6First Prev Next Last Go Back Full Screen Close Quit

=
xk+1 = xk (f 00(xk ))1f 0(xk ).
, ,
.
{xk }
x
f .
-7First Prev Next Last Go Back Full Screen Close Quit

17 f (
l > 0),
: x, y Rn
kf 00(x) f 00(y)k L kx yk,
q = Lkf 0(x0)k/2l2 < 1. xk x
k

k
k

2
kx x k (2l/L)q .
-8First Prev Next Last Go Back Full Screen Close Quit

:
,
,
,
. ,

.

-9First Prev Next Last Go Back Full Screen Close Quit

f (x) inf n
xR

(1)

ei = (0, . . . , 0, 1, 0, . . . , 0) i-
,
x0 , 0 > 0
.
xt Rn ,
t > 0 ,
, 0 < < 1 .
-10First Prev Next Last Go Back Full Screen Close Quit

.
.

. k-
(k 1) n + 1.
kn.
t,
(k 1) n + 1 t kn.

(2)

-11First Prev Next Last Go Back Full Screen Close Quit

f (xt1 +t1 et(k1)n) < f (xt1), (3)



xt = xt1 + t1 et(k1)n, t = t1.
(4)

-12First Prev Next Last Go Back Full Screen Close Quit

f (xt1 t1 et(k1)n) < f (xt1), (5)



xt = xt1 t1 et(k1)n, t = t1.
(6)
(3) (5), t
.
-13First Prev Next Last Go Back Full Screen Close Quit

t , :xt = xt1,

t1, t = kn,

,
t =
t1, t 6= kn


(7)

-14First Prev Next Last Go Back Full Screen Close Quit

k-
.

f (xt1 + t1 ei) f (xt1),


f (xt1 t1 ei) f (xt1),
i = 1, . . . , n.

(8)

-15First Prev Next Last Go Back Full Screen Close Quit

18. f (x)
Rn f C 1(Rn),
, M (x0) = {x Rn :
f (x) f (x0)} .
xk

.

-16First Prev Next Last Go Back Full Screen Close Quit


f (x) min

xQ

(1)

Q = {x Rn | i(x) 0, i = 1, ..., m}
(2)

Fk (x) = f (x)+Pk (x) minn, k = 1, 2, . . .
xR

(26)
Pk (x) Q.
-17First Prev Next Last Go Back Full Screen Close Quit

. Pk (x) Q, Pk (x) 0
k = 1, 2, . . . , x Rn

0,
x Q
lim Pk (x) =
+, x
/ Q,
k
Pk (x) = kH(x), k ,

-18First Prev Next Last Go Back Full Screen Close Quit

H(x) =

m
P
i=1

[i(x)]2+ H(x) =

m
P

[i(x)]+

i=1

([a]+ = max(0, a)).

-19First Prev Next Last Go Back Full Screen Close Quit

xl = x(kl)
(26) l.
l+1. (26) kl+1 > kl. H(xl+1) ,
,
.

-20First Prev Next Last Go Back Full Screen Close Quit

:
1. H : Rn R H(x)
0, x Rn,
2. H(x) = 0 x Q = {x|i(x)
0, i = 1, . . . , m}
3. f , Q

-21First Prev Next Last Go Back Full Screen Close Quit

19. :
(a). f (xk ) + {xk } Q, kxk k +
(b). Q H(xk ) +
{xk }, kxk k +
1). xl


; 2). H(xl) 0
-22First Prev Next Last Go Back Full Screen Close Quit

:
x1 = x1(k1), x2 = x2(k2), . . . , xl = xl(kl), . . .
=
.
, ,
(1)(2)
:
-23First Prev Next Last Go Back Full Screen Close Quit

Fk (x) = f (x)+ak B(x) minn, k = 1, 2, . . .


xR

(30)
B(x) , ak > 0
, ak 0 k .
. B(x) Q, B(x) ,
IntQ
lim B(x) = +.
xQ

: B(x) = +, x Q( ).
-24First Prev Next Last Go Back Full Screen Close Quit

:
m
m
m
X
X
X

i(x)1,
|i(x)|1,
|i(x)|2.
i=1

i=1

i=1

: (30)
: xk+1 = xk k f 0(xk ), k
0.
xk IntQ, k
xk+1 IntQ.
, x0 IntQ,
, xk
(1)-(2)
-25First Prev Next Last Go Back Full Screen Close Quit

xk (30) k
xk IntQ.
(k + 1).
(30) ak+1 <
ak . ak+1B(xk+1) , . .

-26First Prev Next Last Go Back Full Screen Close Quit

:
1.Q ;
2.IntQ 6= ;
3. x Q Q;
4. f Rn;
5. B(x)
IntQ.

-27First Prev Next Last Go Back Full Screen Close Quit

20. :
(a). f (xk ) + {xk } Q, kxk k +
(b). Q .
1) xk


; 2) ak B(xk ) 0
-28First Prev Next Last Go Back Full Screen Close Quit

1.
: 15
20, 10 11.

-29First Prev Next Last Go Back Full Screen Close Quit

.15.

Z1
f (x + y) = f (x) +

hf 0(x + y), yi d,


hf 0(x), yi:
-30First Prev Next Last Go Back Full Screen Close Quit

f (x+y) = f (x)+hf 0(x), yi+

Z1

hf 0(x+ y)

f 0(x), yi d.
x y, , xk
f 0(xk ).
f (xk+1) f (xk ) + hf 0(xk ), f 0(xk )i+
-31First Prev Next Last Go Back Full Screen Close Quit

Z1
+

|hf 0(xk f 0(xk )) f 0(xk ),

f 0(xk )i|d . . .

.
- |ha, bi|
kak kbk
-32First Prev Next Last Go Back Full Screen Close Quit

f (xk ) kf 0(xk )k2 + +

Z1

kf 0(xk

f 0(xk )) f 0(xk )kkf 0(xk )kd . . .



f (xk ) kf 0(xk )k2+
Z1
+ Lk f 0(xk )k kf 0(xk )kd =
0
-33First Prev Next Last Go Back Full Screen Close Quit

,
= f (xk )kf 0(xk )k2+L2 kf 0(xk )k2

Z1

d =
0

= f (xk ) (1 L/2)kf 0(xk )k2 =


= f (xk ) kf 0(xk )k2
( = (1 L/2)) = > 0

-34First Prev Next Last Go Back Full Screen Close Quit

f (xk+1) f (xk ).
s
s
X
f (xs+1) f (x0)
kf 0(xk )k2.
k=0

, f (x)
f >

-35First Prev Next Last Go Back Full Screen Close Quit

s
X

kf 0(xk )k2 (f (x0) f (xs+1))/

k=0

(f (x0) f )/.
f 0(xk ) 0 k . 

-36First Prev Next Last Go Back Full Screen Close Quit

10. (37),
-
f (x + y) f (x) kf 0(x)kkyk + lkyk2/2.
lkyk/2
f (x+y) f (x)+lkyk/2(kyk2kf 0(x)k/l).
= y : kyk > r = 2kf 0(x)k/l
f (x+y) > f (x), ,
B(x, r). 
-37First Prev Next Last Go Back Full Screen Close Quit

. 11.
(37) y x x.
f (x) f (x) + hf 0(x), x xi+
+lkx xk2/2 0.
p

0
kf (x)/ 2l + l/2(x x)k2 =
kf 0(x)k2/2l+hf 0(x), xxi+lkxx)k2/2
-38First Prev Next Last Go Back Full Screen Close Quit

0 f (x) f (x) + hf 0(x), x xi+


+lkx xk2/2.

:
kf 0(x)k2 2l(f (x) f (x)).

-39First Prev Next Last Go Back Full Screen Close Quit

.16 f
x ( 13).
19 :
f (xk+1) f (xk ) (1 L/2)kf 0(xk )k2
,
kf 0(xk )k2 2l(f (xk ) f (x)) ( 14)

f (xk+1) f (xk )l(2L)(f (xk )f (x))


,
-40First Prev Next Last Go Back Full Screen Close Quit

f (x) , :
f (xk+1) f (x) (1 l(2 L))
(f (xk ) f (x))
(38)
q1 = 1 l(2 L). (38) =
f (xk+1) f (x) q1k+1(f (x0) f (x))
(39)
f 6= const ( )
f = const.
-41First Prev Next Last Go Back Full Screen Close Quit

f 0(x) = 0 f (x + y)
2/2
f (x)+hf 0(x), yi+lkyk2/2 lkyk

0 l > 0
= x0 ,
f (x0) > f (x).
k = 0 ( (38))
0 f (x1) f (x) q1(f (x0) f (x)).
-42First Prev Next Last Go Back Full Screen Close Quit

q1 0. q1 < 1,
(39) ,
f (xk ) f (x).

f (x + y) f (x) + hf 0(x), yi + lkyk2/2
y (xk x) x x.

-43First Prev Next Last Go Back Full Screen Close Quit

, x , , , f 0(x) = 0,
(f (xk ) f (x)) lkxk xk2/2.
(39) :
kxk xk2 2q1k (f (x0) f (x))/l.

kxk xk Cq k ,
q

C = 2(f (x ) f (x ))/l, q = q1.


First-44Prev Next Last Go Back Full Screen Close Quit


. ,
xk x k . 

-45First Prev Next Last Go Back Full Screen Close Quit

.18. (1)
x Rn (. ): (3)(7) =
f (xt) f (xt1), t = 1, . . . , =
{xt} M (x0) lim f (xt) f = f (x).
t

lim t = 0.

-46First Prev Next Last Go Back Full Screen Close Quit

: t = > 0, t t0 (..
).
0)|u = xt0 +

M
=
{u

M
(x

ri ei, ri = 0, 1, 2, . . . , i = 1, . . . , n}
i

.
, t0
n
.
xt xt+1.
-47First Prev Next Last Go Back Full Screen Close Quit

.. f (xt) > f (xt+1),


=
M
=
M (x0)
=
t
=
limt t = 0.
-48First Prev Next Last Go Back Full Screen Close Quit

k1 < k2 < < km < . . .


, (8).
.. {xk } M (x0) M (x0) , ,
b.
lim xkm m + x
(8)
m hf 0(xkm + km km ei), km eii =
= f (xkm + km ei) f (xkm ) 0 =
-49First Prev Next Last Go Back Full Screen Close Quit

fx0 i (xkm +km km ei) 0, i = 1, . . . , n,


0 km 1.
,
m hf 0(xkm km km ei), km eii =
= f (xkm km ei) f (xkm ) 0
, , m i = 1, . . . , n
fx0 i (xkm km km ei) 0,
0 km 1.

-50First Prev Next Last Go Back Full Screen Close Quit

, fx0 i (x) Rn. :


b
lim km = 0, lim xkm = x

m
m
m fx0 i (xkm +km km ei) 0, i = 1, . . . , n
m fx0 i (xkm km km ei) 0, i = 1, . . . , n
fx0 i (b
x) = 0, i = 1, . . . , n.
-51First Prev Next Last Go Back Full Screen Close Quit

b
= f 0(b
x) = 0 = x
, .. f . 

-52First Prev Next Last Go Back Full Screen Close Quit

. 19. ,
. (a): Q ,
. {xk }
Q: kxk k +. f (xk ) +.
M (x0) = {x|x Q, f (x)
f (x0)} =
x.
(b) .
-53First Prev Next Last Go Back Full Screen Close Quit

k1 < k2 < < kl < kl+1 < . . .


( )

Fl+1(xl+1) = f (xl+1) + kl+1H(xl+1) >


> f (xl+1)+klH(xl+1) f (xl)+klH(xl) =
= Fl(xl), ..
Fl+1(xl+1) > Fl(xl) l

(27)

-54First Prev Next Last Go Back Full Screen Close Quit

xl xl+1
f (xl) + klH(xl) f (xl+1) + klH(xl+1)
f (xl+1)+kl+1H(xl+1) f (xl)+kl+1H(xl)
, ,
(kl+1 kl)H(xl+1) (kl+1 kl)H(xl)
=
-55First Prev Next Last Go Back Full Screen Close Quit

H(xl+1) H(xl) l
l

(28)

f (xl) f (xl)+klH(xl) f (x)+klH(x),

f (xl) Fl(xl) f (x) l

(29)

(28) (29)
b .
{xl}. x
-56First Prev Next Last Go Back Full Screen Close Quit

liml+ f (xl) = f (b
x) f (b
x) f (x).
(27), (29) = {Fl(xl)}
F f (x) =
f (xl) + klH(xl) F l +
=

lim klH(xl) = F f (b
x) =

l+

b Q, f (x) f (b
H(b
x) = 0, .. x
x)
b . 
f (b
x) = f (x) = x
-57First Prev Next Last Go Back Full Screen Close Quit

. 20. (1)-(2)
x Q (
).
x1, x2, . . . , xk , . . . ,
a1, a2, . . . , ak , . . .
.
k
f (x) f (xk ) f (xk )+ak B(xk ) = Fk (xk )
(31)
> 0
e IntQ: f (e
x
x) f (x) +
-58First Prev Next Last Go Back Full Screen Close Quit

= f (x) + +
+ak B(e
x) f (e
x) + ak B(e
x) Fk (xk )
(32)
xk , xk+1
ak > ak+1
Fk (xk ) = f (xk ) + ak B(xk ) > f (xk )+
+ak+1B(xk ) f (xk+1)+ak+1B(xk+1) =
= Fk+1(xk+1)
.. {Fk (xk )}kN
(31), lim Fk (xk ).
-59-

First Prev Next Last Go Back Full Screen Close Quit

.. lim ak B(e
x) = 0, (32)
k

lim Fk (xk ) f (x) + .

.. > 0, (31)
lim Fk (xk ) = f (x),

lim fk (xk ) = f (x),

lim ak B(xk ) = 0.

-60First Prev Next Last Go Back Full Screen Close Quit

xk (
(a), (b) ).
b.
xk x
f = f (b
x) = f (x).
b Q.
Q k xk Q = x
,
xk . 

-61First Prev Next Last Go Back Full Screen Close Quit

Оценить